The Effect of Providing Oketani Massage in Increasing Breast Milk Production in Post Partum Mothers at The Pratama Nining Pelawati Clinic - Meria Turnip; Desika Wali Pardede; Indah Aprilidayani; Titin Novayanti Dey; Santa Natalia (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Breast milk production in post partum mothers can be increased through various methods, namely aromatherapy, oxytocin massage and oketani massage. Oketani massage is a massage that can increase breast milk production by increasing the strength of the pectoralis muscles, resulting in softer and more elastic breasts, making it easier for babies to breastfeed. When mothers have a positive perception of the use of oketani massage, they feel more confident and see an increase in their baby's ability to breastfeed compared to before. The aim of this research is to determine the effect of giving oketani massage on increasing breast milk production (ASI) in post partum mothers at the Pratama Nining Pelawati Clinic. The data collection technique was carried out using an incidental sampling technique. The method used is quasi-experimental with a one group pretest-posttest design. Data were analyzed using the Wilcoxon test and presented in narrative and table form. The results of the study showed that there was an effect of giving oketani massage in increasing breast milk production in Post Partum mothers at the Pratama Nining Pelawati Clinic with p-value = 0.004 (p<0.05). It is recommended that health workers consider implementing oketani massage as part of a postpartum care program to increase breast milk production